Resource Allocation for Vertical Sectorization in LTE-Advanced Systems - Lei Song; Mugen Peng; Yan Li (International Journal of Antennas and Propagation)
Massive multiple input multiple output (MIMO) technology has been discussed widely in the past few years. Three-dimensional MIMO (3D MIMO) can be seen as a promising technique to realize massive MIMO to enhance the performance of LTE-Advanced systems. Vertical sectorization can be introduced by means of adjusting the downtilt of transmitting antennas. Thus, the radiowave from a base station (BS) to a group of user equipments (UE) can be divided into two beams which point at two different areas within a cell. Intrasector interference is inevitable since the resources are overlapped. In this paper, the influence of intrasector interference is analyzed and an enhanced resource allocation scheme for vertical sectorization is proposed as a method of interference cancellation. Compared with the conventional 2D MIMO scenarios, cell average throughput of the whole system can be improved by vertical sectorization. System level simulation is performed to evaluate the performance of the proposed scheme. In addition, the impacts of downtilt parameters and intersite distance (ISD) on spectral efficiency and cell coverage are presented.